Redefining Disease Severity with Special Area Involvement and Reflecting on Treatment Patterns in a Real-World Psoriasis Population - Mary E. Horner; Kate K. Orroth; Junjie Ma; Yinkang Duan; Myriam Cordey (Adis, Springer Healthcare, 2024)
Abstract Background The International Psoriasis Council (IPC) recommends an approach that considers body surface area (BSA), involvement in special areas, and treatment history for classifying patients as candidates for topical or systemic treatment. This study aimed to quantify the burden of psoriasis by describing BSA distribution, special area involvement, and treatments in a real-world population. Methods This retrospective cohort study included patients with psoriasis from the Optum® deidentified Electronic Health Records database with a BSA value (< 3%, 3-10%, and > 10%) recorded between 1 March 2014 and 1 September 2020. Treatments and special area involvement (face, scalp, palms/soles, nails, genitals) were identified within 90 days of the BSA value and stratified by BSA category. Results Among eligible patients (N = 5120), mean age was 51.4 years and 49.3% were women. The majority of patients (78.9%) were treated with any topical. Proportions of patients with BSA < 3%, 3-10%, and > 10% were 23.4%, 41.9%, and 34.6%, respectively; proportions with 0, 1, and 2+ special areas were 21.6%, 31.6%, and 45.7%, respectively; and 44.4%, 45.7%, and 45.9% of patients with BSA < 3%, 3-10%, and > 10%, respectively, had 2+ special areas. Conclusion The IPC classification can likely identify many more patients who may benefit from systemic therapy than BSA alone. Graphical Abstract